Development of islets of Langerhans in pancreas of neonatal alpacas - Rodríguez G., José (2015)
The aim of this study was to determine the postnatal development of Islets of Langerhans (IL) in alpacas of 0 to 45 days of age. The animals were divided in nine age groups with range of five days. The mumber of IL varied from 3.03 to 4.46 in 10x fields (with an ocular of 10x), the IL diameter varied from 67.89 to 72.55 μm, the number of β cells in the IL from 23.79 to 47.08 and other cells from 18.15 to 39.93. Moreover, the insulin receptor and the transport protein GLUT-2 were observed by immunohistochemistry on the first day of life. It is concluded that the number and size of IL increased with age (p<0.05) while β cells do not show the same trend.